2020
DOI: 10.21203/rs.3.rs-39241/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Anxiety and Uterine Artery Doppler Flow in Pregnant Women with High Risk of Down syndrome: A Prospective Cohort Study

Abstract: Abstract Background: Maternal anxiety may lead to unfavorable pregnancy outcomes, but the underlying mechanism is unclear. This study aimed to evaluate the correlation between maternal anxiety and uterine blood flow index in pregnant women with high risk of Down syndrome undergoing amniocentesis.Methods: This prospective cohort study was conducted at 15-18 weeks of gestational age on 199 pregnant women with high-risk of Down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The increased Doppler indices observed in this study could be attributed to a number of factors discussed in the international literature. Stress hormone levels 34,35 and transient changes in maternal hormone concentrations 14 14 in uence uterine blood ow parameters. The current study found that PI and RI levels were higher in MR pregnant sheep than in LR pregnant sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The increased Doppler indices observed in this study could be attributed to a number of factors discussed in the international literature. Stress hormone levels 34,35 and transient changes in maternal hormone concentrations 14 14 in uence uterine blood ow parameters. The current study found that PI and RI levels were higher in MR pregnant sheep than in LR pregnant sheep.…”
Section: Discussionmentioning
confidence: 99%